Experimental study of an organic Rankine cycle with a variable-rotational-speed scroll expander at various heat source temperatures. (1st May 2023) - Hsieh, Jui-Ching; Chen, Yen-Hsun; Hsieh, Yi-Chi
Abstract: In this study, an organic Rankine cycle with R134a as the working fluid was developed, and a variable-rotational-speed dual expander was used. To improve the cycle performance at various heat source temperatures, the expander was operated in single-expander (SE) and dual-expander (DE) modes at different rotational speeds. Although the electrical output became unstable when the superheat degree was insufficient, it improved when the heat source temperature increased and the expander rotational speed reduced. At a low heat transfer rate, reducing the expander rotational speed effectively decreased the refrigerant mass flow rate and increased the evaporation pressure. In DE mode, the isentropic efficiency ranged from 55.8% to 65.8%. A performance map was created to divide the operating region into three subregions depending on heat transfer rate: 10–17 kW in SE mode at 900 rpm, 18–26 kW in SE mode at 1350 rpm, and ≥27 kW in DE mode at 900 rpm. During a dynamic test conducted at a low heat transfer rate, when the operating mode was switched to SE mode at 900 rpm, the cycle performance was 66% and 108% higher than that in SE mode at 1800 rpm and that in DE mode at 900 rpm, respectively. Highlights: A 2-kW ORC with variable rotational speed and dual expanders has been constructed. Evaporation pressure and flow rate of refrigerant affected by expander rotational speed. A performance map was created to divide the operating region into three subregions. Cycle performance of 900 rpm was 66% higher than that of 1800 rpm at low heat transfer rate. DE mode and high rotational speed suitably operated at high heat transfer rate.